Proteomic profiling of giant skeletal muscle proteins. (4th March 2019) - Murphy, Sandra; Dowling, Paul; Zweyer, Margit; Swandulla, Dieter; Ohlendieck, Kay
ABSTRACT: Introduction : Distinct subtypes of contractile fibres are highly diverse in their proteomic profile and greatly adaptable to physiological or pathological challenges. A striking biochemical feature of heterogeneous skeletal muscle tissues is the presence of a considerable number of extremely large protein species, which often present a bioanalytical challenge for the systematic separation and identification of muscle proteomes during large-scale screening surveys. Areas covered : This review outlines the proteomic characterization of skeletal muscles with a special focus on giant proteins of the sarcomere, the cytoskeleton and the sarcoplasmic reticulum. This includes an overview of the involvement of large muscle proteins, such as titin, nebulin, obscurin, plectin, dystrophin and the ryanodine receptor calcium release channel, during normal muscle functioning, swift adaptations to changed physiological demands and changes in relation to pathobiochemical insults. Expert commentary : The proteomic screening and characterization of total muscle extracts and various subcellular fractions has confirmed the critical role of large skeletal muscle proteins in the regulation of ion homeostasis, the maintenance of contraction-relaxation cycles and fibre elasticity, and the stabilisation of supramolecular complexes of the muscle periphery and cytoskeletal networks of contractile fibres. These findings will be helpful for the future functional systems analysis of giant muscle proteins.